RESEARCH ON THE UPGRADING PATH OF CHINA'S MANUFACTURING INDUSTRY FROM THE PERSPECTIVE OF GLOBAL VALUE CHAINZHANG (Journal of Technology and Operations Management, 2021)
Since joining the world trade organization, China has not only become the largest exporter and trading country in the world, but also one of the countries with the largest increase in the participation of global value chains. However, China's manufacturing industry is facing the situation of transformation and upgrading and is in urgent need of leaping to the high end of the global value chain. Aiming at solving this problem, this essay focused on the study from available literature, data, and reports from various media and CNKI, used Global Value Chain and Digital Economy as the framework to search relevant issues and contribute to how to solve the problem. The results show that the following two ways may be helpful for China to upgrade its manufacturing industry: 1. Promote service-oriented industries; 2. Improve the imbalance of industry supply and demand; 3. Reduce the international dependence.